Two Unrecorded Penicillium Species from Rhizosphere Soil in Korea - Min Kyung Kim; Geon Sik Seo; Myung Soo Park (한국균학회지)
Penicillium perform important ecological functions in the rhizosphere, however, only a relatively small number of Penicillium species have been reported from rhizosphere soils. During a study on Penicillium diversity in Korea, we isolated Penicillium strains from the rhizosphere soils of coniferous and broad-leaved trees. Based on phylogenetic analysis of the β-tubulin and calmodulin loci, we accordingly identified two Penicillium species previously unrecorded in Korea: P. nucicola and P. yarmokense. In this paper, we provide comprehensive morphological descriptions of these two species.